UNEMPLOYMENT FORECAST IN ROMANIA ON THE SHORT-TERM - Mihaela, SAVU; Delia, TESELIOS (Strategii Manageriale, 2014)
This paper presents two ways of forecasting the number of unemployed. One method is the one used by the National Commission for Prognosis, and the second is proposed by the authors and uses the absolute average change. The obtained results predict an increase in the number of unemployed in the next four years in Romania. Figures obtained through the proposed method are contrary to the values given by the National Commission for Prognosis, which shows a decrease of the indicator between 2013-2016. The economic situation of our country makes us believe that a reduction in the number of unemployed is beneficial, but difficult to achieve in the current period.